Efektivitas Metode Wafa Berbasis Otak Kanan dalam Pembelajaran Membaca Al-Qur’an pada Peserta Didik Kelas 1 SDIT Al-Fatih Pangkajene - Karmila Karmila (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Teaching early grade students to read the Quran requires methods appropriate to their developmental characteristics. This study aims to analyze the effectiveness of the right-brain-based Wafa method in teaching Quran reading to first-grade students at SDIT Al-Fatih Pangkajene. This study used a descriptive qualitative approach with a case study design. Data were obtained through observation, interviews, and documentation involving the principal, teachers, homeroom teachers, and students. Data analysis was conducted through data collection, data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and methods.The results showed that the Wafa method was implemented through enjoyable, systematic, and multisensory learning. The teacher used songs, hand gestures, colorful visual media, letter cards, audio murottal (recitation of Quranic verses), repetition, and positive reinforcement to help students recognize the hijaiyah letters, recite them, and build reading confidence. Observations showed that most students were enthusiastic, happy, and active, and were able to master the basics of the hijaiyah letters. This method also strengthens students' learning motivation, self-confidence, and emotional connection with the Quran. Thus, the right-brain-based Wafa method has proven to be relevant as an effective, enjoyable, and appropriate Quranic learning strategy for early elementary school students.